2012
DOI: 10.1002/jps.22746
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of CD40 Signal and Induction of TGF-β by Phosphatidylinositol Mediates Reduction in Immunogenicity Against Recombinant Human Factor VIII

Abstract: Factor VIII (FVIII) is an important coagulation cofactor and its deficiency causes Hemophilia A, a bleeding disorder. Replacement therapy using recombinant FVIII is currently the first line of therapy for Hemophilia A, but the development of neutralizing antibody is a major clinical complication for this therapy. Recently, it has been shown that FVIII associated with Phosphatidylinositol (PI) containing lipidic nanoparticles reduced development of neutralizing antibodies in Hemophilia A mice (1). Here, we inve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 29 publications
0
21
1
Order By: Relevance
“…22 Again, the present analysis has not considered treatment-related factors, which may in some cases modulate the inhibitor risk. The SNPs located in immunoregulatory genes previously associated with inhibitor risk in independent cohorts [6][7][8][9][10][11][12] were not consistently associated with risk in this investigation and in the meta-analysis combining all 3 cohorts. Among these previously described candidates, the SNP at location Ϫ1082A/G in the promoter region of IL-10 is the most frequently reported finding.…”
Section: Pcgf2 Rs2879097contrasting
confidence: 54%
See 1 more Smart Citation
“…22 Again, the present analysis has not considered treatment-related factors, which may in some cases modulate the inhibitor risk. The SNPs located in immunoregulatory genes previously associated with inhibitor risk in independent cohorts [6][7][8][9][10][11][12] were not consistently associated with risk in this investigation and in the meta-analysis combining all 3 cohorts. Among these previously described candidates, the SNP at location Ϫ1082A/G in the promoter region of IL-10 is the most frequently reported finding.…”
Section: Pcgf2 Rs2879097contrasting
confidence: 54%
“…Indeed, genetic markers have been reported, independent of the type of F8 mutation, such as single nucleotide polymorphisms (SNPs) in the genes coding for IL-1, IL-2, IL-10, TNFA, TGF␤, and CTLA-4. [6][7][8][9][10][11][12] Because several of the SNPs characterized in immunoregulatory molecules coded by the human genome will influence the level of immune modulators, immune system challenges in conjunction with replacement therapy and a genetic predisposition might interact. This is supported by the observations of brother pairs and monozygotic twins with discordant inhibitor status 5 and the formation of inhibitors in association with significant inflammatory reactions among patients considered to be at low risk.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, PEG may shield PI and thus negate the immunoregulatory effects of PI. Recently, we showed that PI can downregulate the expression of costimulatory signals in antigen presenting cells (APCs), suppress T cell activation, and increase the secretion of regulatory cytokines such as TGF-beta (57). Further, after intravenous administration, liposomes are in direct contact with the spleen, promoting exposure to B cells.…”
Section: Discussionmentioning
confidence: 99%
“…These are summarized in Table 1. [40][41][42][43][44][45][46][47][48][49][50][51][52] Based on current understanding, it seems unlikely that a single marker of significantly greater importance than multiple others will be identified. In fact, the associations found between polymorphic genes and inhibitory antibodies have not been consistent across study cohorts, and the question, of course, is why?…”
Section: Immune Response Genesmentioning
confidence: 99%